2018
DOI: 10.1016/j.nuclphysb.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ballistic charge transport in the half-filled 1D Hubbard model

Abstract: Whether in the thermodynamic limit of lattice length L → ∞, hole concentration m z η = −2S z η /L = 1 − ne → 0, nonzero temperature T > 0, and U/t > 0 the charge stiffness of the 1D Hubbard model with first neighbor transfer integral t and on-site repulsion U is finite or vanishes and thus whether there is or there is no ballistic charge transport, respectively, remains an unsolved and controversial issue, as different approaches yield contradictory results. (Here S z η = −(L − Ne)/2 is the η-spin projection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 123 publications
(439 reference statements)
2
24
0
Order By: Relevance
“…We thus give a comprehensive picture of temperature-dependent transport and response in the one-dimensional Hubbard model. The present discussion thus complements existing studies that have addressed transport in the one-dimensional Hubbard model using rigorous bounds on transport coefficients, [100][101][102][103][104] and via numerical simulations [100,[105][106][107][108][109][110][111][112][113]. It also substantially extends previous GHD results [55,81] by studying superdiffusion, crossovers in spin dynamics, and the associated experimental signatures.…”
Section: Introductionsupporting
confidence: 73%
“…We thus give a comprehensive picture of temperature-dependent transport and response in the one-dimensional Hubbard model. The present discussion thus complements existing studies that have addressed transport in the one-dimensional Hubbard model using rigorous bounds on transport coefficients, [100][101][102][103][104] and via numerical simulations [100,[105][106][107][108][109][110][111][112][113]. It also substantially extends previous GHD results [55,81] by studying superdiffusion, crossovers in spin dynamics, and the associated experimental signatures.…”
Section: Introductionsupporting
confidence: 73%
“…Nevertheless, some rigorous results have been obtained at half filling. It has been shown in (Carmelo et al, 2018) that for any U > 0 and any positive temperature T > 0 and within the canonical ensemble where N = N ↑ + N ↓ − L is held fixed (while L → ∞), one has a strict upper bound on the charge Drude weight…”
Section: B Charge Conductivitymentioning
confidence: 99%
“…Several early studies reported evidence for a finite Drude weight (Fujimoto and Kawakami, 1998;Kirchner et al, 1999). This result was later challenged by Bethe-ansatz studies that emphasized symmetry constraints on the diagonal matrix elements of the charge-current operator (Carmelo et al, 2013(Carmelo et al, , 2018. Numerically, charge transport was studied using exact diagonalization and MCLM (Prelovšek et al, 2004), finite-T tDMRG (Karrasch et al, 2016(Karrasch et al, , 2014a, dynamical typicality (Jin et al, 2015) and tDMRG simulations of open quantum systems (Prosen andŽnidarič, 2012).…”
Section: B Charge Conductivitymentioning
confidence: 99%
“…[263] remains solvable by the BA. Its coupling to the charge/η-spin and spin degrees of freedom the flux Φ reads Φ = Φ ↑ = Φ ↓ and Φ = Φ ↑ = −Φ ↓ , respectively [263,264]. The LWSs momentum eigenvalues, P(Φ ↑ , Φ ↓ ), have the general form [264],…”
Section: Charge (And Spin) Current Carriers and The General C ηN Bands (And Sn Bands) Hole Representationmentioning
confidence: 99%